Comment on Dysmenorrhea, a Narrative Review of Therapeutic Options [Letter] - Li J; Zhang Y; Tong Y (Journal of Pain Research, 2024)
Jianing Li,1 Yongsheng Zhang,2 Ying Tong3 1Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of China; 2Harbin Institute of Technology, Harbin, People’s Republic of China; 3First Affiliated Hospital, Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of ChinaCorrespondence: Ying Tong, Email tongying@hljucm.edu.cn